Pathogenesis of Molluscum Contagiosum: A new concept for the spontaneous involution of the disease - Khalifa E. Sharquie; Ammar F. Hameed; Waqas S. Abdulwahhab (Our Dermatology Online, 2015)
Background: Molluscum contagiosum is a common viral skin disease that usually has a self-clearing course. Objectives: to study the process of involution of molluscum contagiosum through utilizing histological examination. Patients and Methods: Different sizes and stages of evolution of lesions from 50 patients with molluscum contagiosum were included. Deep shave biopsies were taken from each patient for histopathological examination. Results: All lesions showed a single punctum and this was confirmed by histopathological examination. Each individual lesion showed an epidermal hyperplasia consisting of many lobes which subdivided into lobules that contain the molluscum bodies. The intra-cytoplasmic molluscum inclusion bodies increase in the number and size as the cells differentiate toward the surface of the epidermis to accumulate at a central meeting point equivalent to the clinical sign of umblication at which the infected cells undergo cytocidal disintegration releasing its viral contents into the skin surface. The general histological architecture resemble that of keratoacanthoma. Conclusion: The central umblication represent the site of the future involution that contains the final growth phase of the infected epidermal cells where it ends by a process of cellular death and disintegration releasing its viral contents into the surface of the skin at the craterform opening which is called punctum. This process of self-involution may resemble that of keratoacanthoma where there are many similar pathological features in both conditions.